REKLAMASI PANTAI DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 2014 TENTANG PENGELOLAAN WILAYAH PESISIR DAN PULAU PULAU KECIL - Sodik, Miftahol Fajar; Rofiqi, Imam (2023)
The beauty of nature and all geological ecosystems is a gift from Almighty God which was created for humanity as subjects to manage, use and be responsible for preserving all the beauty of the third planet called Earth, so that all living creatures that inhabit that place can live in mutualistic symbiosis. Irresponsible use and exploitation of natural resources is a threat in living together so that it is not uncommon to find land dredging, conversion of functions and even beach reclamation which can result in natural disasters and imbalance in the geological ecosystem. In this journal, we will explain how legal provisions (formal juridical) protect and regulate the use of natural resources in contact with oceans and beaches, so in this case the author uses an approach and study method of applicable legal rules (positive law) by explaining the contents of the law. -laws that regulate the extent of legal protection for the use of nature in a civil society.